Cardiac Phenotype and Tissue Sodium Content in Adolescents with Defects in the Melanocortin System - Puder, Lia; Roth, Sophie; Krabusch, Philipp; Wiegand, Susanna; Opitz, Robert; Bald, Martin; Flück, Christa; Schulz, Esther; Voss, Egbert; Markó, Lajos; Linz, Peter; Berger, Felix; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: Pro-opiomelanocortin (POMC) and the melanocortin-4 receptor (MC4R) play a pivotal role in the leptin-melanocortin pathway. Mutations in these genes lead to monogenic types of obesity due to severe hyperphagia. In addition to dietary-induced obesity, a cardiac phenotype without hypertrophy has been identified in MC4R knockout mice. Objective: We aimed to characterize cardiac morphology and function as well as tissue Na+ content in humans with mutations in POMC and MC4R genes. Methods: A cohort of 42 patients (5 patients with bi-allelic POMC mutations, 6 heterozygous MC4R mutation carriers, 19 obese controls without known monogenic cause, and 12 normal weight controls) underwent cardiac magnetic resonance (CMR) imaging and 23Na-MRI. Results: Monogenic obese patients with POMC or MC4R mutation respectively had a significantly lower left ventricular mass/body surface area (BSA) than nonmonogenic obese patients. Left ventricular end-diastolic volume/BSA was significantly lower in POMC-and MC4R-deficient patients than in nonmonogenic obese patients. Subcutaneous fat and skin Na+ content was significantly higher in POMC-and MC4R-deficient patients than in nonmonogenic obese patients. In these compartments, the water content was significantly higher in patients with POMC and MC4R mutation than in control groups. Conclusion: Patients with POMC or MC4R mutations carriers had a lack of transition to hypertrophy, significantly lower cardiac muscle mass/BSA, and stored more Na+ within the subcutaneous fat tissue than nonmonogenic obese patients. The results point towards the role of the melanocortin pathway for cardiac function and tissue Na+ storage and the importance of including cardiologic assessments into the diagnostic work-up of these patients.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiac function; left ventricular function; MC4R; melanocortin pathway; Monogenic obesity; POMC; tissue sodium content; tissue water content